Faktor- Faktor Yang Mempengaruhi Kejadian Diabetes Melitus Di Puskesmas Bintuhan Kabupaten Kaur Tahun 2022 - Nursa, Gusmiati; Fauzi, Yusran; Habibi, Julius (Universitas Dehasen Bengkulu, 2022)
Intoduction: Diabetes is a serious chronic disease that occurs when the pancreas does not produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannot effectively use the insulin it produces. Data on Diabetes Mellitus Patients at the Bintuhan Health Center in 2019 recorded 87 cases, in 2020 the number of diabetes mellitus sufferers increased to 94 people and there was a significant increase again in 2021, namely 98 diabetes mellitus sufferers. This very significant increase is the problem of the incidence of diabetes mellitus at the Bintuhan Health Center. The aim of the research is to find out the factors that influence the incidence of diabetes mellitus at the Bintuhan Health Center, Kaur Regency, in 2022. This type of research is descriptive quantitative with an analytic survey research method using a Cross Sectional design. The sample in the study was 97 people with a total sampling technique. The research instrument uses a questionnaire sheet. The research analysis used univariate and bivariate analysis with the chi square test. The results showed that there was a relationship between genetics (p value=0.003), knowledge (p value=0.000), obesity (p value=0.001) and the incidence of diabetes mellitus at the Bintuhan Health Center, Kaur Tahun District. Suggestions, it is necessary to explore the knowledge of respondents related to the incidence of diabetes mellitus so that interventions in the field to increase the knowledge of respondents are more appropriate.